Relation of infarction location and volume to vertigo in vertebrobasilar stroke - Ahmed Mohamed Elhfnawy; Mervat Abd El‐Raouf; Jens Volkmann; Felix Fluri; Doaa Elsalamawy (Brain and Behavior, 2020)
Abstract Objective Vertigo is a common presentation of vertebrobasilar stroke. Anecdotal reports have shown that vertigo occurs more often in multiple than in single brainstem or cerebellar infarctions. We examined the relation between the location and volume of infarction and vertigo in patients with vertebrobasilar stroke. Methods Consecutive patients with vertebrobasilar stroke were prospectively recruited. The infarction location and volume were assessed in the diffusion‐weighted magnetic resonance imaging. Results Fifty‐nine patients were included, 32 (54.2%) with vertigo and 27 (45.8%) without vertigo. The infarction volume did not correlate with National Institute of Health Stroke Scale (NIHSS) score on admission (Spearman ρ = .077, p = .56) but correlated with modified Rankin Scale (ρ = .37, p = .004) on discharge. In the vertigo group, the proportion of men was lower (53.1% vs. 77.8%, p = .049), fewer patients had focal neurological deficits (65.6% vs. 96.3%, p = .004), patients tended to present later (median [IQR] was 7.5 [4–46] vs. 4 [2–12] hours, p = .052), numerically fewer patients received intravenous thrombolysis (15.6% vs. 37%, p = .06), and the total infarction volume was larger (5.6 vs. 0.42 cm3, p = .008) than in nonvertigo group. In multivariate logistic regression, infarction location either in the cerebellum or in the dorsal brainstem (odds ratio [OR] 16.97, 95% CI 3.1–92.95, p = .001) and a total infarction volume of >0.48 cm3 (OR 4.4, 95% CI 1.05–18.58, p = .043) were related to vertigo. In another multivariate logistic regression, after adjusting for age, sex, intravenous thrombolysis, serum level of white blood cells, and atrial fibrillation, vertigo independently predicted a total infarction volume of >0.48 cm3 (OR 5.75, 95% CI 1.43–23.08, p = .01). Conclusion Infarction location in the cerebellum and/or dorsal brainstem is an independent predictor of vertigo. Furthermore, larger infarction volume in these structures is associated with vertigo. A considerable proportion of patients with vascular vertigo present without focal neurological deficits posing a diagnostic challenge. National Institute of Health Stroke Scale is not sensitive for vertebrobasilar stroke.